REFLEXION – A NECESSARY STEP IN THE PROCESS OF SOLVING MATHEMATICS PROBLEMS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The rapid development of modern computer science, including artificial intelligence, significantly contributes to the development of engineering technologies. This progress also requires the education of human resources and constant upgrading of qualifications throughout life. However, there are certain problems in the education of future specialists - read - students, which can be seen at the base of fundamental mathematical education. Looking at the national level of Latvia, this is the insufficient number of students in engineering specialities. Another significant problem is the students' incomplete level of mathematical knowledge and excessive reliance on computer technologies. The mathematical preparation of a specialist plays an essential role - one must be able to detect and evaluate possible errors in software, data input and data interpretation, where such errors can lead to critical, even dangerous situations. An engineer must understand the technological process and be able to perform the appropriate mathematical calculations without the use of technology. Evaluation of the obtained results is an essential part of critical thinking, which must be developed during studies. The goal of the current research is to find out whether students analyse the information and evaluate the results of their work, and how the accuracy of the work design impacts the solution. The authors analysed midterm and final exam papers of engineering students to see how they reflected the ability to evaluate the results obtained. The analysis is based on the examination papers of the students of the Faculty of Natural Sciences and Technology of RTU and the Maritime Academy of RTU, which were written during the study of the calculus course.